Implementation of Online Patient Reservation Registration at Hospital - Irmayani Irmayani; Rosita Ginting; Surya Darma; Dwi Handayani (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2026)
The development of information technology has encouraged digital transformation in healthcare services, including patient registration systems in hospitals. The implementation of online registration systems aims to improve service efficiency, reduce patient waiting times, and facilitate public access to healthcare services. Grandmed Hospital Lubuk Pakam has implemented an online patient registration system through the Mobile JKN application and the E-Reservation Grandmed system. However, the utilization of this system is still not optimal compared to direct registration at the hospital counter. This study aimed to analyze the implementation of the online patient reservation registration system at Grandmed Hospital Lubuk Pakam based on system quality, information quality, and service quality aspects. This study employed a qualitative approach using a case study design. Data were collected through in-depth interviews, observation, and documentation. The informants were selected using purposive sampling and consisted of three participants. The collected data were analyzed using qualitative analysis through the stages of data reduction, data presentation, and conclusion drawing. The results showed that the implementation of the online patient reservation registration system at Grandmed Hospital Lubuk Pakam has generally been well implemented. In terms of system quality, the use of the Mobile JKN application and E-Reservation Grandmed facilitates patient registration and helps reduce queues at the registration counter. Regarding information quality, the information provided by the system is relatively clear and easy for patients to understand, although real-time updates are not fully implemented. In terms of service quality, the online registration system improves service efficiency and provides convenience for patients in scheduling hospital visits. In conclusion, the implementation of the online patient reservation registration system at Grandmed Hospital Lubuk Pakam has a positive impact on improving healthcare service efficiency. Therefore, improving system stability, updating information regularly, and increasing patient education regarding the use of the online registration system are necessary to optimize its utilization.